Chronic kidney disease, heart failure and neprilysin inhibition. Issue 4 (26th April 2019) - Haynes, Richard; Zhu, Doreen; Judge, Parminder K; Herrington, William G; Kalra, Philip A; Baigent, Colin
Abstract: Patients with chronic kidney disease are at increased risk of cardiovascular disease and this often manifests clinically like heart failure. Conversely, patients with heart failure frequently have reduced kidney function. The links between the kidneys and cardiovascular system are being elucidated, with blood pressure being a key risk factor. Patients with heart failure have benefitted from many trials which have now established a strong evidence based on which to base management. However, patients with advanced kidney disease have often been excluded from these trials. Nevertheless, there is little evidence that the benefits of such treatments are modified by the presence or absence of kidney disease, but more direct evidence among patients with advanced kidney disease is required. Neprilysin inhibition is the most recent treatment to be shown to improve outcomes among patients with heart failure. The UK HARP-III trial assessed whether neprilysin inhibition improved kidney function in the short- to medium-term and its effects on cardiovascular biomarkers. Although no effect (compared to irbesartan control) was found on kidney function, allocation to neprilysin inhibition (sacubitril/valsartan) did reduce cardiac biomarkers more than irbesartan, suggesting that this treatment might improve cardiovascular outcomes in this population. Larger clinical outcomes trials are needed to test this hypothesis.